2010
DOI: 10.1108/17538271011063889
|View full text |Cite
|
Sign up to set email alerts
|

The Ghanaian transaction‐based residential indices

Abstract: PurposeThe purpose of this paper is to provide technically robust indicators of housing market performance from the records held by the Ghana Land Valuation Board, through the construction of the first ever residential price and rent indices for the aggregate and disaggregate markets.Design/methodology/approachThe approach involved time series produced from hedonic models using 3,250 transaction‐based data, running from 1992 to 2007, and documents on movements in capital and rental values in Accra and Tema, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Previous studies suggested submarket existence based on several market segmentations (Schnare & Struyk 1976;Goodman 1978;Allen et al 1995;Fletcher et al 2000;Goodman & Thibodeau 2007;Anim-Odame et al 2010a;Anim-Odame et al 2010b;Wu & Sharma 2012;Wheeler et al 2014). The results suggest that submarkets exist for a structural segmentation of the market than for a full span of spatial segmentation.…”
Section: _______________________________________________________ 259mentioning
confidence: 72%
See 3 more Smart Citations
“…Previous studies suggested submarket existence based on several market segmentations (Schnare & Struyk 1976;Goodman 1978;Allen et al 1995;Fletcher et al 2000;Goodman & Thibodeau 2007;Anim-Odame et al 2010a;Anim-Odame et al 2010b;Wu & Sharma 2012;Wheeler et al 2014). The results suggest that submarkets exist for a structural segmentation of the market than for a full span of spatial segmentation.…”
Section: _______________________________________________________ 259mentioning
confidence: 72%
“…The 18 th AFRES ANNUAL CONFERENCE 2018 analysis and this is very useful in appreciating market dynamics and making market predictions (Wheeler et al 2014). Housing markets research continues to receive little attention from researchers and research in this area is characterised by data unavailability and asymmetries (Anim-Odame et al 2010a;Anim-Odame et al 2010b).…”
Section: _______________________________________________________ 236mentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical work has mostly adopted the ETV model to construct hedonic indices largely because the model is easy and simple to use (Anim-Odame et al, 2010;Wilhelmsson, 2009). There is the need to empirically examine the accuracy of these two models, especially in thin markets where the number of transactions per period are typically small.…”
Section: Hedonic Price Indices For Developing Marketsmentioning
confidence: 99%